2017
DOI: 10.1186/s12943-017-0596-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in cancer stem cells

Abstract: Compelling evidence have demonstrated that bulk tumors can arise from a unique subset of cells commonly termed “cancer stem cells” that has been proposed to be a strong driving force of tumorigenesis and a key mechanism of therapeutic resistance. Recent advances in epigenomics have illuminated key mechanisms by which epigenetic regulation contribute to cancer progression. In this review, we present a discussion of how deregulation of various epigenetic pathways can contribute to cancer initiation and tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
242
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(266 citation statements)
references
References 301 publications
1
242
0
7
Order By: Relevance
“…Chromatin structure defines the state in which genetic information in the form of DNA is organized (Toh et al, 2017). Recent advances in cancer research have shown that global changes in the epigenetic landscape are a hallmark of various types of malignant diseases, including prostate cancer (PCa) (Jeronimo et al, 2011;Baylin, 2002, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin structure defines the state in which genetic information in the form of DNA is organized (Toh et al, 2017). Recent advances in cancer research have shown that global changes in the epigenetic landscape are a hallmark of various types of malignant diseases, including prostate cancer (PCa) (Jeronimo et al, 2011;Baylin, 2002, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…27 As a pluripotent transcription factor, SOX2 is expressed in CSCs of many types of tumors to induce and maintain their pluripotency and tumorigenic ability. 28 Recently, it is also reported to be required for the initiation and growth of melanoma CSCs. 16 Here, we demonstrate that SOX2 is also sufficient and necessary for the induction of melanoma SP cells.…”
Section: Discussionmentioning
confidence: 99%
“…More understanding about these signaling pathways could contribute to the design and development of new therapeutic platforms. In this context, epigenetic regulations appeared as key modulators in cancer and CSCs [65][66][67][68][69][70]. MicroRNAs (miRNAs) are one of main epigenetic regulators which act as oncogenes or tumor suppressors [71][72][73][74][75][76][77][78].…”
Section: Diagnosis and Treatment Of Pcmentioning
confidence: 99%